Coping strategies, work-life balance programs, and their impact on professional performance of female lecturers in tertiary institutions in Anambra and Enugu States - Adaobi Jennifer Iloakasia (Indonesian Journal of Learning and Educational Studies, 2024)
The dual responsibilities of career and parenting place significant demands on female lecturers, particularly in tertiary institutions, where academic expectations often collide with family obligations. In Anambra and Enugu States, female lecturers face unique challenges in balancing these roles, with many experiencing stress, burnout, and anxiety due to time constraints and societal expectations. The study used a descriptive survey approach to examine the coping strategies of female lecturers managing career and parenting responsibilities in tertiary institutions in Anambra and Enugu States, southeastern Nigeria. A total of 2,297 respondents from colleges of education, universities, and polytechnics participated. Data were collected using a validated 4-point Likert scale questionnaire, the "Scale for Balancing Psychological Impacts of Career and Parenting" (SBPICP), with a reliability coefficient of 0.76. Descriptive statistics summarized demographic characteristics and pressures faced by participants. Non-parametric tests, including the Kruskal-Wallis and Jonckheere-Terpstra tests, were used to examine differences in perceptions based on marital status and age. Decision trees were also considered to explore nonlinear relationships in the data. The findings reveal that female lecturers face significant challenges in balancing career and parenting, including anxiety, burnout, stress, and time constraints. These challenges are exacerbated by societal expectations and family responsibilities, which negatively affect their psychological well-being and professional performance. Although work-life balance programs exist, their effectiveness in addressing these stressors remains limited, particularly in terms of childcare options and institutional support. The study also identifies various coping strategies employed by female lecturers, including time management and social support, as crucial in mitigating the negative impacts. Based on these findings, the study recommends the implementation of more comprehensive and targeted work-life balance programs, such as flexible working hours and childcare facilities, to enhance the well-being and professional performance of female lecturers.